Karakterisasi Mineral Magnetik Batuan Peridotit Daerah Awang Bangkal Kabupaten Banjar Kalimantan Selatan Menggunakan Metode XRD dan King - Shinta Khalidah; Sudarningsih Sudarningsih; Ibrahim Sota (Jurnal Fisika FLUX, 2012)
Study the nature of magnetism in rocks that has been carried out at theresearch of peridotite rocks in Awang Bangkal Banjar Regency has not finished,still need to do further research. More specific details of research has been done isabout the characterization of the magnetic minerals in peridotite rocks in the areaAwang Bangkal, Banjar Regency, South Kalimantan, which aims to identify thetype of magnetic minerals, characterize magnetic minerals including multidomain,single domain or pseudo single domain and the estimate magnetic mineral’s grainsize. This study uses XRD test to find out the existing content of magnetic mineralsin peridotite samples, the method of King (the ratio between the magneticsusceptibility with the anhysteretic susceptibility) and decay AnhystereticRemanent Magnetization (ARM) to estimate the grain size of magnetic minerals inperidotite samples. XRD results show that the magnetic minerals contained in theperidotite samples are hematite and magnetite. The ARM decaying curve showedthat the estimated peridotite rocks in the research are multidomain to pseudosingledomain and the size are big. While the distribution of grain size betweenbelow 0.1 μm up to ≈ 5 μm.